KOI Pond: The “Elevator Pitch” that Adapts to Describe the Breadth and Variety of Clinical Informatics Practice - Manning, John D.; Wang, Michael; Sarabu, Chethan; Goonan, Kelly; Toth, William R.; Bell, Elijah J.; Pearson, John F.; Levy, Bruce P. (ACI Open, 2020)
Background The practice of clinical informatics (CI) is diverse and frequently tailored to individual skills and interests or to organizational/departmental needs. Prior studies have sought to define core content areas, educational milestones, and practice patterns within the clinical informatics subspecialty (CIS). Unfortunately, no single tool or framework currently exists that can succinctly define an informatician's role regardless of setting. The diversity of informatics practice makes it difficult to have one “pitch” that describes all possible domains, tasks, knowledge, and skills available to an informatician.Objective Using qualitative data from multiple informaticians, provide a succinct framework to describe and compartmentalize the various functions an informatician can contribute to the healthcare field.Methods We created an iterative focus group of five CIS fellows enrolled in different fellowship programs nationwide, one CIS program director, and an MD-PhD candidate in biomedical informatics. After much discussion, iteration, and consideration of career options within a young and burgeoning subspecialty, a dual-axis model was created that describes CIS practice in terms of settings (internal, external, and policy) and focus areas (knowledge, operations, and innovation).Results and Conclusion By combining both axes into a single “KOI pond” and then prioritizing sections by interest/resource investment, we are able to generate a unique snapshot for each informatician. These snapshots can be used (1) by informaticians to characterize their own practice succinctly as a pitch, (2) by CIS fellows who are considering career options, and (3) by those unfamiliar with CIS who want to learn more.
Keywords: academic training; clinical informatics; professional activity study; career mobility; medical informatics applications